Are the more educated receiving more training? Evidence from Thailand - Kenn Ariga; Giorgio Brunello (Fondazione Eni Enrico Mattei (FEEM), 2002)
This paper investigates the relationship between education and training provided by the firm, both on the job and off the job, using a unique dataset based on a survey of Thai employees conducted in the summer of 2001. We find a significant and negative relationship between educational attainment and on the job training and no significant relationship between education and off the job training. We also find that education and training are technical complements, especially in the case of off the job training. These findings are consistent with more educated individuals having higher marginal costs of training than less educated workers, especially where on the job training is concerned. Either the better educated have lower learning skills in jobs requiring on the job training or they have higher opportunity costs of training, or both.
Keywords: J24; J31; 330; Training; education; wages; Hochqualifizierte Arbeitskräfte; Betriebliches Bildungsmanagement; Berufsbildung; Ungelernte Arbeitskräfte; Schätzung; Thailand